Pengembangan Modul Materi Cahaya Berbasis PBL4C Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Sekolah Penengah Pertama - A’irin Nurwidyastuty (Jurnal Didaktika Pendidikan Dasar, 2020)
The purpose of this study is to describe the process and results of module development, the objectives and competencies to be achieved, the strengths and weaknesses of the module, and the improvement of critical thinking skills after using the module. Module development by using the 4D model that is define, design, develop and assess produce PBL4C (Problem Based Learning the 4 Core Areas) modules. The material validation score is 3.31, the design validation score is 3.51, the language validation score is 3.47 which means that the module is stated valid. Modules are also developed in the Android application so students can study anywhere, anytime, with anyone. PBL4C is PBL which is an integration of multi-disciplinary knowledge, multi-dimensional skills, correct thoughts and universal harmonious values. Based on research data that is normality test, amounting to 0.131 with Asymp. Sig. (2-tailed) of 0.179 with a value of p> 0.05, so it can be concluded that the data are normally distributed. Homogeneity test results stated the value of F = 1.072 and p value> 0.05 (sig. (0.422)> 0.05) means the distribution of homogeneous data. Based on hypothesis testing using T test p value (.000) <0.05. H0 is rejected and H1 is accepted which means the module can improve students' critical thinking skills.